'Death from all sides': spectacle, morality, and trauma in Suzanne Collins' the Hunger Games trilogy. (2nd October 2021) - Moffat, Kirstine; May, Melody
ABSTRACT: Suzanne Collins' bestselling Hunger Games trilogy is saturated in death, particularly the death of children. In exploring these fictional deaths, this article firstly considers the problematic nature of Collins' representation. While the trilogy's declared purpose is to critique the misuse of power by a corrupt government who perpetuate their control through staging the slaughter of children as entertainment, the narrative can only make this critique through itself enacting the gladiatorial contest which is the Hunger Games. The tension between the Hunger Games as voyeuristic spectacle and as murder of innocents is never fully resolved, but Collins' awareness of the cost and trauma of murder and war mitigate this seeming exploitation of human suffering. Drawing on Susan Sontag's interrogation of both the dangers and necessity of representing violent death in Regarding the Pain of Others, we argue that Collins depicts and confronts death to critique oppressive power and its devaluing of life. Through her protagonist Katniss, Collins articulates a message of action in the face of terror and loss, while never losing sight of the tragic cost of violence. Her complex and nuanced engagement with death seeks to sensitise her audience and heighten their ethical awareness as they follow Katniss's moral evolution.